Mapping Policy Actors for Enhanced Engagement Towards Agroecology Transition: Case of Tunisia - Ouerghemmi, Hassen; Frija, Aymen; M. Oumer, Ali; Dhehibi, Boubaker; Ryan, Nehring (International Center for Agricultural Research in the Dry Areas, 2023)
In this brief, we explore the food system actors (FSAs) of the one CGIAR initiative in Tunisia , from a policy engagement lens. We particularly want to explore the level of policy influence of all food system stakeholders engaged within the initiative in 2022 and 2023. Stakeholder engagement here can be of different forms ranging from attending key consultation meetings, to trainings and capacity development, etc. We identify the distinct policy roles played by each one of these FSAs by referring to a robust methodology used to label each of these actors based on its level of policy influence (Dhehibi et al., 2023). Based on that, and by comparing annual policy engagement of the OneCGIAR agroecology initiative in Tunisia across 2022 and 2023, we identify the main gaps in terms of participation of key policy actors to our initiative and build on that for strengthen representation of these important actors along our implementation process in 2024 and 2025.